2007
DOI: 10.1186/gb-2007-8-8-r175
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and pseudoautosomal localization of the major histocompatibility complex in monotremes

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. The major histocompatibility complex in monotremes

The characterization and chromosomal mapping of major histocompatibility complex (MHC)-containing BAC clones from platypus and the short-beaked echidna reveals new insights into the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…The majority of orthology with the chicken genome was to the Z (represented by regions of HSA 5 and 9), which was represented by 11 BACs distributed along X 5 and the long arm of X 3 . Recent studies (Dohm et al 2007;Rens et al 2007) have also identified small regions of homology with the chicken Z on X 2p and distal X 1p .…”
Section: Gene Content Of Bacs On Platypus Sex Chromosomesmentioning
confidence: 97%
See 1 more Smart Citation
“…The majority of orthology with the chicken genome was to the Z (represented by regions of HSA 5 and 9), which was represented by 11 BACs distributed along X 5 and the long arm of X 3 . Recent studies (Dohm et al 2007;Rens et al 2007) have also identified small regions of homology with the chicken Z on X 2p and distal X 1p .…”
Section: Gene Content Of Bacs On Platypus Sex Chromosomesmentioning
confidence: 97%
“…2). In addition, four genes/BACs from recent mapping studies were included in our analysis (Dohm et al 2007;Rens et al 2007; see Table 1). This confirms the order of the chromosomes in the chain and provides new information on the XY pairing (pseudoautosomal) regions.…”
Section: Identification and Localization Of Bacs On Platypus Sex Chromentioning
confidence: 99%
“…The echidna has an equally complex sex chromosome system, and it was shown that the sex chromosomes of the platypus and echidna share homology but are not identical; the echidna has five X and four Y chromosomes, sharing seven with the platypus. In the echidna, an autosome replaces one of the platypus X chromosomes, and the X 5 homologue in echidna has a central position in the chain instead of being at the end, as in platypus (Dohm et al, 2007;Rens et al, 2007).…”
Section: Marsupial Sex Chromosomesmentioning
confidence: 99%
“…5). The scattering of homologies to the chicken Z chromosome extending from X5 to X1 was predicted by the translocation model in Gruetzner et al 2006 and is supported by the disruption of the MHC region onto two sex chromosome pairs (Dohm et al 2007), and importantly by the fact that different autosomes have been added to the sex chromosome complex in platypus and echidna independently (Rens et al 2007). Given this evidence, Crspx/Crspy likely have differentiated on heteromorphic sex chromosomes before X autosome translocations led to this sex chromosome complex (Fig.…”
Section: Evolution Of Crspx and Crspymentioning
confidence: 71%
“…Eight sex chromosomes share homology between platypus and echidna (Tachyglossus aculeatus) showing that this system evolved early in the monotreme lineage (Rens et al 2007). Additional autosome-sex-chromosome translocations in the echidna and platypus lineage occurred after their divergence over 25 Million years ago (Rens et al 2007;Dohm et al 2007;Warren et al 2008). There are two fundamentally different scenarios to explain the evolution of this complex system (Gruetzner et al 2006).…”
Section: Introductionmentioning
confidence: 99%